STUDY AND MODELING OF SOLVENT INFLUENCE ON ISOSALIPURPOSIDE EXTRACTION FROM HELICHRYSI ARENARII FLOWERS - N. N. Boyko; D. I. Pisarev; E. T. Zhilyakova; O. O. Novikov (Фармация и фармакология (Пятигорск))
This article presents results of the study and modeling of solvent influence on isosalipurposide extraction from Helichrysi Arenarii flowers.The aim of this work is to study the influence of the solvent on isosalipurposide extraction from Helichrysi arenarii flowers and suggest a theoretical model for description of the results obtained.Materials and methods. The basic materials were: a ground plant raw material of Helichrysi arenarii flowers. water solutions of ethanol (26, 43, 59, 72, 81, 97±1% v/v.), methanol, 1-propanol, 2-propanol, acetone and ethyl acetate. The extracts were obtained from the plant raw materials / solvent at the ratio of 1:5 (wt./vol.) by maceration for 24 hours at the temperature of 24±1°С. The analysis of the extracts was carried out by reversed-phase high performance liquid chromatography and isosalipurposide reference substance.Results and discussion. A dependence of isosalipurposide concentration in ethanol-water extracts on ethanol concentration in the solution was studied. It has been found out that maximum concentration of isosalipurposide is observed in the solutions with ethanol concentration of 75±5% v/v. This range of ethanol concentrations corresponds to solvent’s dielectric constant value of 38±3 units. The regression equation of dependence between isosalipurposide concentration in the extract and dielectric constant of ethanol-water solution has been obtained. Optimal concentration of the solvent has been theoretically predicted and experimentally verified as in the case of   water solutions of methanol, acetone, 1-propanol, and 2-propanol.Conclusion. It has been determined that solvent’s dielectric constant has the most significant influence on the extraction process of phytocompound from the plant raw material. A mathematical model for description of the dependence of isosalipurposide concentration on dielectric constant of ethanol-water solutions has been substantiated theoretically and tested. The optimal range of solvent’s dielectric constant to obtain maximum concentration of isosalipurposide in the extract has been found.